Female and Male Students' Perceptions of Cooperative Learning in the Fields of Educational Sciences and Counselling - Alireza Ahmadi; Mohammad Reza Keramati; Javad Por Karimi (Comparative Education Society of Iran ( CESIR), 2021)
Despite the importance of cooperative learning in university classrooms, few studies have been conducted as a comparative form in terms of field of study and gender. Therefore, the present study seeks to study the perception of students of Educational sciences and Counselling from cooperative learning in university classrooms in terms of disciplines and gender. In this study two classes in the field of Educational sciences and Counseling at the University of Tehran were selected. Qualitative data were collected through unstructured interviews and data were analysed using Atlas-ti Software. The analysis of students' descriptions of implementing cooperative learning in classroom environment showed four categories including quality of learning, life skills, classroom environment, and opportunities for improvement. Findings indicated that female students paid more attention to the quality of learning and male students paid more attention to opportunities for improvement. However, the percentage of participants' attention to the quality of learning in the cooperative learning class was more than the other three categories. University instructors can turn challenges into an opportunity to improvement by proper implementation of cooperative learning in university classrooms. Also Counselling students paid more attention to opportunities for improvement than Educational sciences students.  Findings of this study have important applications in improving the quality of teaching methods of faculty members. The results, while encouraging instructors to learn more about cooperative learning, provide new insights for them about students' interests and concerns. The findings of the study encourage faculty members to turn the challenges into an opportunity for their teaching improvemen